Students response toward development of e-module in physics material on respiratory system - Desy Purwasih; Erfin Novianti; Jumadi Jumadi (Jurnal Pijar Mipa, 2022)
The aim is to determine the student's response to the Physics E-module material on the respiratory system. The type of research used is Research and Development (R&D). The number of samples was 31 students of class VIII Junior High School 1 Mantewe using the purposive sampling method. The data collection instrument was a student response questionnaire with aspects of perception, belief, and participation. The average results of each study were 3.6, 3.5, and 3.5. The overall average is 3.5, with a very good category. The results showed that all electronic modules were suitable for academic users, as evidenced by students' positive responses to the developed E-modules.